Electrophysiological and Behavioral Evaluation of Auditory Processing in Adults with Dysphonia - Bez, Ana Cláudia Mondini Ribeiro; Luiz, Cyntia Barbosa Laureano; Paes, Sabrina Mazzer; Azevedo, Renata Rangel; Gil, Daniela (International Archives of Otorhinolaryngology, 2020)
Introduction Dysphonia is an oral communication disorder. The voice and hearing are interrelated aspects. Hearing is an important sensory input for monitoring the vocal pattern. The relation between hearing abilities and dysphonia represents a contribution both in scientific and in clinical terms, especially in cases in which satisfactory results are not achieved in the therapeutic process.Objective To characterize long-latency auditory evoked potential (P300) with tonal and complex stimuli, and to make a behavioral evaluation of auditory processing in adults with behavioral dysphonia.Method The sample used for the present study consisted of 20 subjects from both genders with ages ranging from 18 and 58, who were diagnosed with behavioral dysphonia. The evaluations occurred in a single 2-hour session, in which the procedures of clinical history, pure tone and speech audiometries, acoustic immittance measures, and behavioral and electrophysiological evaluations of auditory processing were performed.Results The descriptive measures of P3 latency elicited by tonal and complex stimuli showed similar results for the right and left ears, without statistically significant differences. In the qualitative analysis, the results observed were within the normality patterns for the P3 component for both tonal and complex stimuli. As for the behavioral evaluation of auditory processing, abnormal results were observed in 100% of the sample. Abnormalities were found in the auditory skills of ordering and temporal resolution and figure-background obtained from the duration pattern, random gap detection, and dichotic tests (syllables and words), respectively.Conclusion The evaluated patients presented central auditory processing disorder, evidenced by behavioral assessment.
Keywords: auditory evoked potential; hearing; auditory perception; dysphonia; voice